Nanoparticles: tech trends in healthcare - Chandran, Anu; Raghavan, Varun; Chalil, Bhaskaran; ., Kamalasanan; Velayudhan, C. C.; Zulfiker, Mirvaz; M., Midhun; Rajappan, Sanju; Sreedharan, Sily; ., Deeshma; K., Remash; Binub, Kanniyan (International Journal of Research in Medical Sciences, 2022)
Nanotechnology is the use of matter on an atomic, molecular, and supramolecular scale for various purposes. Nanotechnology field of application is very much diverse which includes surface science, organic chemistry, molecular biology, semiconductor physics, energy storage, engineering, microfabrication, and molecular engineering. Its medical application ranges from biological devices, nano-electronic biosensors, and to future biological machines. The main issue nowadays for nanomedicine involve understanding the issues related to toxicity and environmental impact of nanoscale materials. Lot more functionalities can be added to nanomaterials by interfacing them with biological structures. The size of nanomaterials is similar most biological molecules and so useful for both in vivo and in vitro biomedical research and applications. The integration of nanomaterials with biology had paved path to the development of diagnostic devices, contrast agents, analytical tools, physical therapy applications and drug delivery vehicles.